Defect energetics and nonstoichiometry in lanthanum magnesium hexaaluminate - Park, JG; Cormack, AN (ACADEMIC PRESS INC JNL-COMP SUBSCRIPTIONS, 1997)
Computer-based atomistic simulation methods are applied to address quantitatively the defect energetics and crystal chemistry of lanthanum magnesium hexaaluminate (LMA). The tetrahedral site preference of Mg in the magnetoplumbite structure is determined by calculating lattice energies for different Mg ion distributions. It is revealed that the intrinsic and extrinsic disorders are much influenced by the distribution of Mg in the structure. Our calculations show that oxygen Frenkel disorder is the dominant defect mode to be expected, even though Schottky disorder may also exist. Several feasible defect processes in nonstoichiometric LMA are determined from the enthalpies of the quasi-chemical reactions for the processes with simple point defect energies. We have also modeled some defect complexes in the mirror plane regions. It is found that the Mg ions positioned in the tetrahedral sites suppress the formation of cation vacancies in the mirror plane, through hindering the relaxation of the 12k Al ions by which the vacancies are stabilized. In Mg-deficient nonstoichiometric LMA, however, it is expected that the defect complex [V-La+V-Al+2(V-Al+Al-i)] will be formed in the interspinel layer. Our calculations also indicate that the O-La defect is improbable in LMA not only as a simple point defect but also as a member of a defect complex. (C) 1997 Academic Press.
Keywords: STRUCTURED CERAMIC OXIDES; ELECTRON-SPIN RESONANCE; TUNABLE LASER MATERIAL; SOLID-STATE CHEMISTRY; CRYSTAL-STRUCTURE; CATION DISTRIBUTION; MAGNETOPLUMBITE; ALUMINATE; FLUORESCENCE; LAMGAL11O19